Patterns of body mass index and multiple non-communicable disease risk behaviours among students in universities in Owerri, Imo State, Nigeria - Chiagoziem Ogazirilem Emerole; Salome Nkechinyere Onyeka Ibe; Eunice Anyalewechi Nwoke; Joakin Chidozie Nwaokoro; Chidera Chisom Obasi; Chioma Gloria Emerole; Precious Chinasa Okwu (Discover Public Health)
Abstract Background Non-communicable diseases (NCDs) are chronic diseases of a non-infectious nature that result in unfortunate outcomes such as reduction in quality of life, morbidity, and mortality. Some of the main risk factors associated with NCDs are unhealthy behaviours learned and established at a young age. These include harmful use of alcohol, tobacco use, sedentary lifestyles, and unhealthy diets. This study aims to determine prevailing NCD risk behaviours among university students and their patterns of Body Mass Index (BMI). Methods This was a cross-sectional study among university students attending Imo State University and Federal University of Technology Owerri. Participants were recruited using a systematic multistage sampling method. Data was collected structured questionnaires adapted from the WHO’s STEPS survey. Analysis was conducted with SPSS software at a 0.05 level of significance. Results Findings show that students exhibited notable prevalence rates of these behaviours, with 70.9% reporting regular alcohol consumption, no smoking reported, 63.7% engaged in physical activity, and 100% consuming some level of junk food. There were statistically significant associations between the students' socio-demographic characteristics and certain behavioural risk factors (p < 0.05). Conclusions This study identified key patterns of NCD risk behaviours among university students in Owerri, Nigeria. Findings show high rates of alcohol consumption, unhealthy dietary habits with frequent junk food intake, and a significant prevalence of sedentary behaviour. Physical activity levels were generally low, and BMI results revealed many students were overweight or obese, which increases their risk of NCDs.